L’Homme-toupie. Le vagabond comme figure de la subversion dans Le Ventre de Paris d’Émile Zola - Rachwalska von Rejchwald, Jolanta (Quêtes littéraires, 2014)
A vagrant Florent Quenu serves as a methaphor of social-political shift that strikes France in the late XIX-th century. Intimidated by the magnitude of change, upon his return Florent wanders the streets, meanders and strolls in circles which casts a horrendous contradiction with the austerity of Hausmann’s new Paris, aligned with omnipresent straight line forms. This geometrical collision of a straight line and a curve is symptomatic of ferocious conflict between the Second Empire and the alternative social model embodied in the Florent’s attitude.